Effect of Extraction Time and Sodium Bisulfite on Citronella (Cymbopogon nardus) Extract: Yields, Moisture, and GC-MS Analysis - Widowaty, Windy; Meidina; Sulistyorini (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2026)
This study investigated the influence of extraction time and sodium bisulfite concentration on citronella (Cymbopogon nardus) extracts using ethanol as solvent. Nine treatments (P1–P9) were evaluated for yield, moisture content, and preliminary TLC screening. The highest yield (59.94%) was obtained at 4 h with 2.5 g sodium bisulfite, while P8 (5 h, 2 g sodium bisulfite) exhibited a lower yield but higher moisture content, suggesting greater solubilization of polar compounds. ANOVA confirmed that extraction parameters significantly affected extract composition (p < 0.05). TLC results, however, produced anomalous Rf values exceeding the theoretical limit, attributed to the use of n-hexane: acetic acid (6:4) as mobile phase, which was unsuitable for terpenoid separation. Consequently, TLC was considered qualitative only. GC–MS analysis of P8 revealed 18 peaks dominated by long chain fatty acids (palmitic, oleic, cis vaccenic acids), while citronella’s characteristic terpenoids (citronellal, citronellol, geraniol) were absent, confirming volatilization losses during ethanol extraction. These findings highlight that ethanol extraction at elevated temperatures yields fatty acid rich fractions with potential functional applications, however, it is unsuitable for producing authentic citronella essential oil. Future work should optimize TLC solvent systems, extend GC–MS profiling to all treatments, and employ alternative extraction methods such as steam distillation or solvent free microwave techniques to preserve volatile terpenoids.